DAMPAK GLOBALISASI KEBUDAYAAN TERHADAP PERUBAHAN PERILAKU WANITA DI INDONESIA - Alam, Dede Rubai Misbahul (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This research discusses the impact of cultural globalization on changes in women's behavior in Indonesia. Globalization is often seen as a competition for business, economics and technological sophistication. In fact, behind everything in globalization it has targeted all aspects of people's lives in Indonesia, including culture. Globalization has had an influence on changes in behavior in society, especially women. Many women have become victims of cultural changes due to the new culture. As a result, many women (Muslim women) are trapped in the mire of globalization; caught up in the current of feminism, human rights, LGBT, giving birth to a culture shock that has destroyed the spirit of women. This research is a literature review where the author uses books, journals and the results of expert analyzes in thought studies and discussions published in scientific works. This research has useful value that is very relevant for improving current conditions which are complicated by the challenges and threats of globalization technology. Among the solutions recommended by the author in this research is that Muslim women can be more alert and not easily trapped in the cultural traps of globalization such as fashion traps, life style, free sex and human rights and technology traps. The author recommends that women can be more active in seeking knowledge and can re-understand their qadrat in maintaining their spirit and nature and become the front guard in family defense.